Sadrazam Mehmed Said Paşa’nın (Küçük) İngiliz Büyükelçiliğine Sığınması (1895) - Emel DEMİR GÖRÜR (Gazi Akademik Bakış)
In this study, Mehmed Said Pasha, an important government man who became grand vizier five times as of the relevant date and one of the important figures of the Sultan II. Abdulhamid period, took refuge in the British Embassy, the reasons for his refuge, and the negotiations between Sultan and Pasha through emissaries and the efforts to convince Said Pasha were discussed in detail. Under the mediation of British Ambassador Sir Philip Currie and under the leadership of the Austrian Ambassador Baron Calice, the involvement of the ambassadors was examined. The study was handled with the Ottoman Archive Documents and British Archive Documents, which contain the correspondence and reports submitted by British Ambassador Currie with the Ottoman and British authorities. To follow the reflections of the issue of the European and especially British public opinion, European-origin newspapers and memoirs were used by taking the precautionary principle into consideration.